Analisis Kebutuhan Perangkat Lunak Sistem Informasi Back Office: Studi Kasus Hublang dan Teknik Perumdam Among Tirto Kota Batu - Ananta, Vennina (Politeknik Negeri Banyuwangi Jl. Raya Jember km. 13 Labanasem, Kabat, Banyuwangi, Jawa Timur (68461) Telp. (0333) 636780, 2022)
Perumdam Among Tirto Kota Batu is a public drinking water company located in Batu City, East Java which runs its business in the field of clean water distribution for the majority of the citizen of Batu City. Perumdam Among Tirto Kota Batu still runs it business manually and has not fully utilized the information system. The development of the information system is needed by the company to be able to increase its productivity. Therefore, it is necessary to analyze the software requirements for the development of information systems that will be used by Perumdam Among Tirto Kota Batu to running its business, especially by the back office. In this research, the results of software requirements analysis for Perumdam Among Tirto Kota Batu back office information system are compiled to Software Requirements Specification (SRS) document using SRS outline that standarized by ISO/IEC/IEEE 29148:2018. The research carried out resulted in seven SRS documents made for seven divisions in Customer Relation and Marketing Departement and also Engineering Departement, that is Customer Service and Water Meter Division, Equipment Service and SR Standardization Division, Information Technology Development and Marketing Division, Engineering Planning Division, Non Revenue Water and Supervision Division, Production, Transmition, and Laboratory Division, and Distribution Division. Each SRS document consist of five part that is Introduction, References, Requirements, Verification, and Appendices as standarize by ISO/IEC/IEEE 29148:2018.